2019
DOI: 10.3390/md17050248
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Activity of PT-Peptide Derived from Anti-Lipopolysaccharide Factor of the Swimming Crab Portunus trituberculatus Is Enhanced when Encapsulated in Milk-Derived Extracellular Vesicles

Abstract: PT-peptide is derived from the anti-lipopolysaccharide factor of the swimming crab Portunus trituberculatus. The peptide, consisting of 34 amino acids, contains a lipopolysaccharide binding domain. In this study, we investigated the effect of PT-peptide encapsulated in raw milk-derived extracellular vesicles (EVs), designated as EVs-PT peptide, on immune regulation. The results showed that raw milk-derived EVs efficaciously delivered the PT-peptide into monocytes and elevated immune activity, including reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…EVs exhibit the potential for encapsulating and transporting different cargo, including proteins, peptides, enzymes, RNA, and DNA. Various organisms (i.e., microorganisms, plants, and animals) secrete EVs, thereby interacting with each other through the exchange of EVs-contained cargo to regulate target gene expression [ 15 , 35 ]. In the past, we have reported that LAB-derived EVs possess the ability to inhibit the growth of pathogenic bacteria [ 9 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…EVs exhibit the potential for encapsulating and transporting different cargo, including proteins, peptides, enzymes, RNA, and DNA. Various organisms (i.e., microorganisms, plants, and animals) secrete EVs, thereby interacting with each other through the exchange of EVs-contained cargo to regulate target gene expression [ 15 , 35 ]. In the past, we have reported that LAB-derived EVs possess the ability to inhibit the growth of pathogenic bacteria [ 9 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tomato-derived EV were isolated by an ultracentrifugation protocol, as described in our previous study with modification. 4,10,18 Tomato samples (Solanum lycopersicum L., cultivar Jade Girl) were purchased from the market in Tainan City of Taiwan. Tomatoes (1 kg) were homogenized in a highspeed blender for 30 seconds, the resulting juice was collected after filtration through a net filter, and then the centrifugation was carried out under the following conditions: 1000g (10 min, 4 °C), 2000g (20 min, 4 °C), 4000g (30 min, 4 °C), and 10 000g (60 min, 4 °C).…”
Section: Isolation Of Tomato-derived Evmentioning
confidence: 99%
“…2,3 In a previous study, we used EV isolated from milk to encapsulate active peptides for improving immunity. 4 Plantderived exosome-like nanovesicles exhibit anti-inflammatory and tumor growth inhibitory properties, nanovesicles isolated from ginger demonstrate the capability to suppress the activation of NLRP3 inflammasome and offer potential preventive effects against inflammatory bowel disease. 5,6 Corn-derived nanoparticles have anti-colon cancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the catalytic activity of the catalase-loaded EVs prepared by different methods followed the same listed order. An analogous procedure was carried out to load the EVs with peptides composed of 34 amino acids [ 50 ]. Among the mentioned conditions, only the incubation time at room temperature was extended to 2 h. The method showed satisfactory results over various EV sizes (26 to 295 nm).…”
Section: Techniques Applicable For Loading Evsmentioning
confidence: 99%